Perkembangan Kognitif Anak Usia Dini Usia 5-6 Tahun di TK Cerdas Ceria - Adiani Hulu; Putri Indah Sari Laia; Tanni Sagala; Tri Arti Panjaitan; Kasih Indah Rejeki Purba; Friskajunita Nababan (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aimed to examine and comprehend the cognitive development of young children, particularly those between the ages of five and six, at Tk Cerdas Ceria. Direct observation of the children's activities and learning process at Tk Cerdas Ceria was used in this study. Teachers' interviews and field reports were used to gather data. The findings demonstrated that children between the ages of 5 and 6 had substantial cognitive development, as seen by improved language use, problem-solving, and logical thinking abilities. Youngsters started to solve basic problems, comprehend cause-and-effect relationships, and classify items. An engaging learning environment, a range of varied learning activities, and the active involvement of parents and instructors all have an impact on this.